2019
DOI: 10.1136/gutjnl-2018-317416
|View full text |Cite
|
Sign up to set email alerts
|

Serine proteases as luminal mediators of intestinal barrier dysfunction and symptom severity in IBS

Abstract: ObjectiveThe intestinal lumen contains several proteases. Our aim was to determine the role of faecal proteases in mediating barrier dysfunction and symptoms in IBS.Design39 patients with IBS and 25 healthy volunteers completed questionnaires, assessments of in vivo permeability, ex vivo colonic barrier function in Ussing chambers, tight junction (TJ) proteins, ultrastructural morphology and 16 s sequencing of faecal microbiota rRNA. A casein-based assay was used to measure proteolytic activity (PA) in faecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 60 publications
4
99
2
Order By: Relevance
“… 32 Briefly, on the day of measurement mice were fasted for 2 h then given a 200 µl oral gavage containing 100 mg/mL creatinine, 60 mg/mL FITC-4 kDa Dextran, and 40 mg/mL of rhodamine B isothiocyanate-70 kDa dextran (Sigma) to allow assessment of pore (radius 2.6 Å), leak (radius 13 Å) and unrestricted (radius 64 Å) barrier pathways, respectively. 32 Mice were fasted for additional 2 h after which food was replaced. Five hours post-gavage, the intracardiac puncture was performed to harvest blood and collect serum samples.…”
Section: Methodsmentioning
confidence: 99%
“… 32 Briefly, on the day of measurement mice were fasted for 2 h then given a 200 µl oral gavage containing 100 mg/mL creatinine, 60 mg/mL FITC-4 kDa Dextran, and 40 mg/mL of rhodamine B isothiocyanate-70 kDa dextran (Sigma) to allow assessment of pore (radius 2.6 Å), leak (radius 13 Å) and unrestricted (radius 64 Å) barrier pathways, respectively. 32 Mice were fasted for additional 2 h after which food was replaced. Five hours post-gavage, the intracardiac puncture was performed to harvest blood and collect serum samples.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, these data have lent some credence to host serine proteases as playing critical roles in controlling the homeostatic network at the mucosal surface of the intestine, while largely dismissing the effect of their bacterial counterparts. A tight regulation of such proteases is though needed since an increased proteolytic activity could be detrimental to the epithelium and impair the intestinal barrier 49,50 …”
Section: Serine Proteases In a Nutshellmentioning
confidence: 99%
“…Moreover, 7 additional serpins (protease inhibition activity, InterPro family IPR000215) were identified with similar abundance in fasted and fed mice. It has been reported that high protease activity measured in the feces of patients suffering from irritable bowel syndrome correlates with a decrease in microbial diversity [62]. It is therefore tempting to speculate that the various serine protease inhibitors detected and identified in EVs produced in mice mono-colonised with Bt (submitted to Vesiclepedia, number) is a consequence of the lack of microbial diversity, and is to counteract the detrimental effect of proteases present in high abundance in the gut lumen [62] of mono-colonised mice.…”
Section: Discussionmentioning
confidence: 99%